2017
DOI: 10.1071/sh16150
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of sex-seeking apps and websites in the social and sexual lives of gay, bisexual and other men who have sex with men: a cross-sectional study

Abstract: Background The objective of this study was to explore the relationship between online sex-seeking, community/social attachment and sexual behaviour. Methods Respondent-driven sampling was used to recruit 774 sexually active gay and bisexual men in Vancouver, Canada, aged ≥16 years. Multivariable logistic regression compared men who had used online sex-seeking apps/websites in the past 6 months (n = 586) with those who did not (n = 188). Results Multivariable results showed that online sex seekers were more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 48 publications
2
18
1
Order By: Relevance
“…As greater sexual sensation seeking and partner frequency have been associated with online sex seeking (Card et al, 2016), these factors likely moderate the relationship between internet dating and CAS (Horvath, Beadnell, & Bowen, 2006; Matarelli, 2013). Likewise, higher treatment optimism and substance use have also been associated with both online sex seeking and risky sexual behavior (Grosskopf, Harris, Wallace, & Nanin, 2011; Rendina et al, 2015; Shilo & Mor, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As greater sexual sensation seeking and partner frequency have been associated with online sex seeking (Card et al, 2016), these factors likely moderate the relationship between internet dating and CAS (Horvath, Beadnell, & Bowen, 2006; Matarelli, 2013). Likewise, higher treatment optimism and substance use have also been associated with both online sex seeking and risky sexual behavior (Grosskopf, Harris, Wallace, & Nanin, 2011; Rendina et al, 2015; Shilo & Mor, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In examining which factors might underlie the association between CAS and online sex seeking, we have previously compared men who seek sex online with those who do not (Card et al, 2016). These earlier findings indicated that online sex seeking MSM tended to be younger, had more Facebook friends, spent more social time with other gay men, were more emotionally attached with the gay community, and had lower communal sexual altruism scores.…”
mentioning
confidence: 99%
“…With the proliferation of apps, increased use of these apps may facilitate finding casual sexual partners, resulting in unsafe sexual practices [ 6 ]. Prior work has shown that MSM who use these apps (app-users) tend to have more sexual encounters, more frequent anal intercourse, more unprotected sex, and a larger number of sexual partners known to have HIV and other STIs [ 7 10 ]. This increases their risk for HIV and STIs acquisition/transmission, compared with MSM who used different channels to seek sex partners (non-users) [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4]17, 20] A number of studies have reported on HIV testing history among gay men and tend to find that men who use apps are more likely to have been tested for HIV. [15,20] Studies in gay men in Australia, suggest that men who use a combination of mobile phone apps, internet websites and offline places to meet partners appear to be at increased risk of STIs or HIV compared with men who use a narrower range of online and offline methods. [21] In women, low annual household income was associated with meeting partners online.…”
Section: Principal Resultsmentioning
confidence: 99%